2004
DOI: 10.1080/08916930310001637977
|View full text |Cite
|
Sign up to set email alerts
|

The L1 Retroelement-related p40 Protein Induces p38δ MAP Kinase

Abstract: We characterized a full length L1 mRNA in a rheumatoid arthritis (RA) synovial tissue and determined the degree of methylation of its 5'-UTR. We asked whether not only intact but also altered L1s can exert biological activities by transfecting RA synovial fibroblasts (SF) with either retrotransposition-competent or incompetent L1s and examined their capacity to induce p38delta. Total RNA was isolated from the synovial tissue of a 35-year-old woman with highly destructive RA. A complete L1 sequence was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 28 publications
0
33
0
2
Order By: Relevance
“…Trex-1 was also detected by immunohistochemistry on paraffin-embedded sections of synovial tissue, as described previously (4)(5)(6). Rabbit anti-Trex-1 polyclonal antibodies (Abcam), goat anti-rabbit biotinylated antibodies, and streptavidin conjugated to alkaline phosphatase were used for tissue staining, and Dako Fast Red substrate was used to reveal the staining.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trex-1 was also detected by immunohistochemistry on paraffin-embedded sections of synovial tissue, as described previously (4)(5)(6). Rabbit anti-Trex-1 polyclonal antibodies (Abcam), goat anti-rabbit biotinylated antibodies, and streptavidin conjugated to alkaline phosphatase were used for tissue staining, and Dako Fast Red substrate was used to reveal the staining.…”
Section: Methodsmentioning
confidence: 99%
“…The promoter of the L1 retroelement is hypomethylated in RASFs (5), reflecting global DNA hypomethylation. The L1-related p40 protein (L1-ORF1p) has nucleic acid binding properties and favors the transcription of specific genes (6). The L1-encoded p150 protein (L1-ORF2p) has a reverse transcription activity, transmobilizing Alu RNA and Pol II transcripts, which yields new autoantigenic, hypomethylated DNA fragments (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gay, synovial tissue DNA in RA patients is hypomethylated, and when normal synovial fibroblasts are treated with the DNMT inhibitor 5-AZA (5-aza-2′-deoxycytidine), they develop a RASF-like phenotype [6,7]. A recently published report also provides evidence of histone hyperacetylation in synovial tissue samples from animals with a RA-like condition compared to animals with osteoarthritis (OA).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Recent studies have shown that phosphorylation-related proteins can be coimmunoprecipitated with ORF1p or L1 RNPs (39,40). In addition, the mitogen-activated protein kinase (MAPK) p38 has been implicated in L1 activation by environmental toxins (41,42), and its expression can be increased by exogenous ORF1p (43). Although large-scale proteomic studies can only identify a subset of phospho sites (44), a phosphoproteomic study of human embryonal stem cells, in which L1 is active, identified an ORF1p fragment phosphorylated on S18 (45).…”
mentioning
confidence: 99%